Constructivism in Online Course Design of Skilled-based Courses and Its Impact on Student Achievement - Pascal Roubides; Adwyn Roubides (Journal of Research in Mathematics, Science, and Technology Education, 2025)
The following monogram presents a research case study involving two sections of an asynchronous online college algebra course which aimed at exploring the potential impact (or lack thereof) of the traditional one-size-fits-all online course design ideology for the development of skilled-based courses at a large higher education institution in Florida, USA. At the principal author’s institution, as appears to be the case in many other sister institutions, constructivism is the philosophical framework upon which all online courses are being built – that occurs without the consideration that the impact of constructivist elements of course design may have little to no effect on student achievement when applied to largely or strictly skilled-based courses. Empirical observations, as well as past experiences in this field, have pointed to the realization that there are many skilled-based courses “sprinkled” with myriads of “little” tasks aimed at conforming to the constructivist ideology that do not appear to add any value in terms of the actual objectives of learning. Therefore, adding such tasks for the mere satisfaction of or adherence to a particular educational ideology may pose an inappropriate, ineffective, and inefficient way to provide and assess learning. Hence, it was the authors’ impetus to investigate what empirical observations in online skilled-based courses alluded to in a structured academic research manner and ascertain mathematically whether such a misalignment exists so as to inform future practice. Results obtained confirmed empirical observations that adding constructivist elements in the asynchronous online college algebra courses analyzed made no difference in overall student success.